Description of a new pest species of Hemilecanium Newstead (Hemiptera: Coccidae) on mango from Thailand, and a key to species of the genus - Kondo, Takumasa; Williams, Michael L. (Zootaxa, 2005)
The adult female and first-instar nymph of a new species of soft scale insect, Hemilecanium mangiferae Kondo & Williams sp. nov., are described and illustrated. This species was collected on the trunk and branches of mango, Mangifera indica L., in Nakhon Pathom and Sukhothai Provinces, Thailand. The insect can cause serious damage by depleting the host sap and by producing large amounts of honeydew on which sooty molds grow. Damage was severe on the local mango cultivar, Nam DokMai. Also included are a revised diagnosis of the genus, a revised key to the adult females of the five species currently placed in the genus, and a key to the known firstinstar nymphs.La hembra adulta y la ninfa del primer estadio de una nueva especie de escama blanda, Hemilecanium mangiferae Kondo & Williams sp. nov., se describe e ilustra. Esta especie fue colectada en el tronco y ramas del mango: Mangifera indica L. en las provincias de Nakhon Pathom y Sukhothai, Tailandia. Este insecto puede causar daños severos al mango deprivando el árbol de savia, y produciendo gran cantidad de melado cual induce el crecimiento de fumaginas. El daño fue más severo en un cultivar local conocido como Nam Dokmai. Tambien se incluyen una diagnosis revisada para el género, una clave revisada para las hembras adultas de las cinco especies actualmente incluidas en el género, más una clave para las ninfas del primer estadio conocidas.